A weak COPI binding motif in the cytoplasmic tail of SARS‐CoV‐2 spike glycoprotein is necessary for its cleavage, glycosylation, and localization - Jennings, Benjamin C. (FEBS Lett, 2021)
The SARS‐CoV‐2 spike glycoprotein (spike) mediates viral entry by binding ACE2 receptors on host cell surfaces. Spike glycan processing and cleavage, which occur in the Golgi network, are important for fusion at the plasma membrane, promoting both virion infectivity and cell‐to‐cell viral spreading. We show that a KxHxx motif in the cytosolic tail of spike weakly binds the COPβ’ subunit of COPI coatomer, which facilitates some recycling of spike within the Golgi, while releasing the remainder to the cell surface. Although histidine (KxHxx) has been proposed to be equivalent to lysine within di‐lysine endoplasmic reticulum (ER) retrieval sequences, we show that histidine‐to‐lysine substitution (KxKxx) retains spike at the ER and prevents glycan processing, protease cleavage, and transport to the plasma membrane.